Interpretation of Normal and Abnormal Tympanogram Findings in Eustachian Tube Dysfunction. (June 2021) - Parsel, Sean M.; Unis, Graham D.; Souza, Spenser S.; Bartley, Heather; Bergeron, Jeffrey M.; Master, Adam N.; McCoul, Edward D.
Objective: To characterize the relationship between objective tympanogram values and patient-reported symptoms and associations with common comorbid conditions. Study Design: Cross-sectional study with prospective data collection. Setting: Tertiary medical center. Methods: Patients undergoing routine audiometric evaluation between October 2018 and June 2019 were included. Participants with temporomandibular joint dysfunction, inner ear hydrops, and similar conditions were excluded. Symptoms were assessed with the 7-item Eustachian Tube Dysfunction Questionnaire. Demographics and medical comorbidities were recorded from the medical record. Analysis of tympanometric peak pressure (TPP), demographics, and comorbidities was performed to determine associations with clinically significant eustachian tube dysfunction (ETD) symptoms. Results: A total of 250 patients were included with similar demographics: 101 (40.4%) in the asymptomatic group and 149 (59.6%) in the symptomatic group. The median (interquartile range) TPP was –10 (20) daPa and –25 (100) daPa in the asymptomatic and symptomatic groups, respectively. A diagnosis of rhinitis was more likely to be associated with significant ETD symptoms (adjusted odds ratio, 2.61; 95% CI, 1.23-5.63). A subgroup analysis revealed that symptomatic patients with normal TPP values were negatively skewed as compared with asymptomatic patients. This symptomatic group had a higher prevalence of rhinitis and chronic rhinosinusitis than the asymptomatic group. Conclusion: Patients with symptoms of ETD may have a TPP within a range typically considered normal per conventional standards. This suggests that the currently accepted interpretation of tympanometry findings may be insensitive for the diagnosis of less severe cases of ETD.